Proposing transmedia storytelling for Malaysian film industry: Thematic considerations - Aziz, Jamaluddin (Penerbit Universiti Kebangsaan Malaysia, 2021)
Media convergence is ultimately the result of the disruption in media technology, creating a new episteme that foregrounds the diverse and interlinked way a story travels across platforms. One crucial development of media convergence is transmedia. While media scholars argue that media convergence has resulted in ontological uncertainties, it ironically entrenches some recognisable functions of the traditional media. This enables traditional communication functions like storytelling to be incorporated within media convergence. Storytelling, as communication functions, has continued to challenge the spatial and temporal metaphors of messages, allowing cultural symbols to transcend traditionally held boundaries in communication. Indeed, much has been written about transmedia storytelling, less however, has linked transmedia storytelling with the Malaysian film industry. The main aim of this paper is to thematically review past studies on transmedia storytelling in order to propose the idea that transmedia storytelling can help the Malaysian film industry as it is a new form of communication that the industry needs in increasing production, creating and determining local and global consumption of Malaysian stories. The review of past studies on transmedia storytelling reveals five salient themes: 1) Transmedia and engagement; 2) Liberatory potential; 3) Hybridisation of producer and user; 4) Uniqueness of media genre, and 5) Media literacy. The themes found are used to problematise transmedia storytelling and the Malaysian Film industry; this leads to the proposal of how transmedia storytelling can help the Malaysian film industry prosper while contributing to the understanding of transmedia storytelling and its benefit for the Malaysian film industry. © 2021, Penerbit Universiti Kebangsaan Malaysia. All rights reserved.